The Influence of Price and Quality of Service on Guest Satisfaction at Sky Lounge The Premiere Hotel Padang - Fadhilla, Diva Dwi; Putra, Trisna (Pt. Threeple Herphi Educate, 2024)
Cost incurred hotel guests as well quality service can influence satisfaction guest . In its implementation sometimes matter This escape from attention hotel management. Research This aiming see influence price as well as quality service to satisfaction guests at Sky Lounge The Premiere Hotel. Study This included in research descriptive quantitative based on method associative causal. Population study This guests who visited Sky Lounge The Premiere Hotel Padang in September 2021 – February 2022. Based on amount existing population as many as 2,918 then technique taking sample in research this is what i use formula Slovin with sample totaling 97 people. Data collection is carried out by communication inadvertently direct or with the spread questionnaire . Instrument research use questionnaire (survey) with compilation based on scale Likert . Trial instrument it's done there right with Validity test method and reliability test. Research results This namely on the price variable show category Enough with percentage 42.3%, then on the variable next on the variables quality service show category Enough with percentage of 44.3% and on the variable satisfaction visitor show category Enough with percentage of 50.5%. The R Square value is 0.165, which means influence variables X1, X2 , and Y as much as 16.5%